Literasi Keuangan, Pendapatan dan Perilaku Keuangan: Dampaknya Terhadap Keputusan Investasi - Jamali, Hisnol; Yunus, Rostiaty; Ningsih, Wahyuni Yusria (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2023)
This research explores the correlation between financial literacy, income, financial behavior, and investment decisions among the STIKES employees. A total of 61 respondents participated in the study using a Likert-scale questionnaire. The data analysis technique employed was Structural Equation Modeling Partial Least Squares (SEM PLS). The research findings indicate that financial literacy has a positive impact, though not significant, on investment decisions. This highlights the importance of financial literacy, albeit not as the primary determinant. Meanwhile, income, despite having a positive effect, also lacks significance in influencing investment decisions. The most striking revelation is the significant and positive influence of financial behavior on investment decisions. Aspects such as regular savings, debt reduction, financial planning, and periodic investment evaluation are crucial in shaping individual investment decisions. This study provides in-depth insights into the factors influencing investment decisions among STIKES employees. The primary implications underscore the need for more attention to developing healthy financial behaviors, offering financial consultation services, and financial education focused on practical practices to assist individuals in managing their investments wisely. These findings can serve as a foundation for designing better financial strategies for STIKES employees and other stakeholders, paving the way for a better future